Analysis Of Multi Lane Free Flow Implementation At Toll Gates In Indonesia (Case Study Of Cililitan Toll Gate 2) - Shefa Salsabila, Nazwa; Nur Azizah, Fitria; Fitriyani, Fitriyani; Novriani, Shinta; Budisiswanto, Nurullah (CV. Green Publisher Indonesia, 2024)
As the volume of vehicles on toll roads and non-toll roads increases, congestion occurs when the road capacity can no longer accommodate the volume of vehicles passing through it. one of the most crowded toll roads in Indonesia is the Jagorawi Toll Road. Congestion often occurs at several points along the Jagorawi Toll Road, especially the Cililitan Toll Gate. Congestion at the Toll Gate often occurs because the level of service at the Toll Gate does not match the level of vehicle arrivals during peak hours. Therefore, in the research “Analysis of Multi lane Free Flow Implementation at Toll Gates in Indonesia (Case Study of Cililitan Toll Gate 2)”, this study aims to determine the performance and impact on vehicles at Cililitan Toll Gate 2 that are still using E-Toll and its effect on Vehicle Operating Costs (VOC) if the E-Toll system and MLFF system are installed at Cililitan Toll Gate 2. Therefore, using the analysis method with the help of Microsoft Excel can analyze data on the performance of E-Toll and VOC and survey data processing using SPSS. Based on the research findings, on Wednesday, March 6, 2024 has a delay time on the E-Toll payment system of 49 seconds. And also obtained the value of VOC when MLFF is applied (at a speed of 60 km / h) is lower than the value of VOC when E-Toll is applied (at a speed of 9.72 km / h) resulting in congestion costs of Rp. 3,653.75 / km for passenger cars, Rp. 1,113.66 / km for medium vehicles, Rp. 4,014.32 / km for large buses and Rp. 8,045.89 / km for large trucks.